2002
DOI: 10.1023/a:1020177409891
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Focus groups with culturally diverse populations, and Latino farmworkers in particular, have been used as an effective research method. However, the specifics of planning and implementing focus groups with diverse populations have not been elaborated in the literature. Focus groups were used as part of The Reducing Pesticide Exposure in Minority Families Project to successfully elicit migrant farmworkers' views on pesticide exposure and preferences for educational method. Although attention was paid to cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…All focus groups were held by AJM, a nurse and bilingual moderator of Somali descent with a PHD degree and significant knowledge of conducting focus groups. When choosing a facilitator of focus group with a diverse cultural background the person need to be respected, credible and preferably a member of the cultural group [ 21 , 22 ]. GEP, a physiotherapist and a Swedish native, kept field notes of the interactions occurring and ensured that everyone had the opportunity to speak.…”
Section: Methodsmentioning
confidence: 99%
“…All focus groups were held by AJM, a nurse and bilingual moderator of Somali descent with a PHD degree and significant knowledge of conducting focus groups. When choosing a facilitator of focus group with a diverse cultural background the person need to be respected, credible and preferably a member of the cultural group [ 21 , 22 ]. GEP, a physiotherapist and a Swedish native, kept field notes of the interactions occurring and ensured that everyone had the opportunity to speak.…”
Section: Methodsmentioning
confidence: 99%
“…Research has suggested that the planning of questions is useful in focus groups involving people from culturally and linguistically diverse backgrounds. In particular, they indicate that questions that were too open failed to yield answers sufficiently detailed to be meaningful [42]. The problem identification and planning phases of action research reported here have facilitated a period of enquiry, which describes, interprets and explains social situations in the setting where change is required.…”
Section: Discussionmentioning
confidence: 99%